2014
DOI: 10.3390/ijms150813681
|View full text |Cite
|
Sign up to set email alerts
|

Robust Non-Wetting PTFE Surfaces by Femtosecond Laser Machining

Abstract: Nature shows many examples of surfaces with extraordinary wettability, which can often be associated with particular air-trapping surface patterns. Here, robust non-wetting surfaces have been created by femtosecond laser ablation of polytetrafluoroethylene (PTFE). The laser-created surface structure resembles a forest of entangled fibers, which support structural superhydrophobicity even when the surface chemistry is changed by gold coating. SEM analysis showed that the degree of entanglement of hairs and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…Recently, Liang et al (2014) have demonstrated that homogeneously texturing poly(tetrafluoroethylene) (PTFE) leads to the formation of an air-trapping porous structure that is effectively superhydrophobic [15]. Since then, our recent work has shown that similar structures can form on a wide variety of polymers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liang et al (2014) have demonstrated that homogeneously texturing poly(tetrafluoroethylene) (PTFE) leads to the formation of an air-trapping porous structure that is effectively superhydrophobic [15]. Since then, our recent work has shown that similar structures can form on a wide variety of polymers [16].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of wetting of a surface by a liquid, leading to the spreading of those liquids over the surface, can be seen as a crucial factor that is adopted within surface chemistry and surface engineering including applications such as biomaterials [1][2][3] and coating technologies [4,5]. As demonstrated in current surface engineering literature, wettability characteristics of many materials can be altered by the means of laser-induced surface treatment [1,6,7] and other surface treatments [8][9][10]. Despite increased academic recognition and demand for greater industrial deployment, wetting and the effects of surface modification are still not fully understood within the engineering community.…”
Section: Introductionmentioning
confidence: 99%
“…These laser-induced structures can be used to alter the wettability of a material, resulting in a more hydrophobic or hydrophilic surface [10,11,26]. Other uses of such laser-induced topographies include surface coloration [27,28], surfaceenhanced Raman scattering (SERS) [29], reduced cell growth [30,31], and improved broadband optical absorption [15,32] for applications such as photovoltaics [33]. A comprehensive review of fs-laser surface texturing on metals has been provided by Ahmmed et al [1].…”
Section: Introductionmentioning
confidence: 99%